Design and implementation of data governance in the company eMan a.s. - Czinner, Michal (2022)
In my final thesis, I deal with the design and implementation of data governance in the company eMan a.s., whose business is a custom software development and which has about 150 employees. Along with the company's continuous growth, especially in recent years, the need for better data governance has emerged to achieve greater confidence in the data and to use the data more effectively for decision-making. In my proposal of activities and areas of data governance, I have been inspired by the DAMA-DMBOK methodology, whose activities and areas are simplified and applied to achieve the expected effects without a significant impact on the company's budget. I have practically applied and verified the results of this work on a sample example from the recruitment example and will apply them in the future to other company processes.